Developing Placebos for Clinical Research in Traditional Chinese Medicine: Assessing Organoleptic Properties of Three Dosage Forms (Oral Liquid, Capsule and Granule) - Xiao, Mengli; Ying, Jiake; Zhao, Yang; Li, Qingna; Zhao, Yingpan; Gao, Rui; Lu, Fang (Frontiers in Pharmacology, 2021)
Background: The successful application of randomized, double-blind placebo-controlled studies requires maximum blinding. Organoleptic properties of the placebo should be similar to the drug, making it difficult to distinguish between the two. Evaluation of the TCM placebo simulation effect can determine whether the preparation of placebo can be genuinely blind in clinical trials. There is still a lack of well-established methods to evaluate TCM placebos. Hence, this study aimed to explore the evaluation methodology of TCM placebo simulation. Methods: An independent evaluation method and three comparative evaluation methods were proposed, and three dosage forms (oral liquid, capsule and granule) were tested. The independent evaluation, in which each person was given an experimental drug or a placebo, gave an overall assessment of organoleptic properties in a blind state. We comparatively evaluated the similarity in organoleptic properties between the experimental drug and placebo. According to different distribution methods, we divided comparative evaluation methods into three. In method 1, the evaluator was given the experimental drug and placebo and was told that there must be a placebo among them. In method 2, each evaluator was randomly assigned to the combination group or two investigational drugs group. In method 3, the evaluator was assigned to a set of three coded samples, numbered by random three-digit numbers, each different, two of which were identical, and the two samples were equally frequent. Results: In the independent evaluation, there was no difference between TCM placebo and experimental drugs in a blind state at the level of P = 0.05. Even though the comparative evaluation methods enabled identification of potential differences between the two samples, methods 2 and 3 were better than method 1 in eliminating psychological factors. Also, in method 3, the completely random method combined with the blind method eliminated the subjectivity and objectivity bias and improved the experiment’s credibility compared with the previous two methods. Conclusions: Regardless of the methods that could evaluate the placebo’s simulated effect in actual clinical trials, we suggest that independent evaluation and comparative evaluation (method 3) should be combined to reflect better whether the placebo is truly blind.